Demografia e variação genética de Puma concolor (Linnaeus, 1771) na região nordeste do estado de São Paulo - Miotto, Renata Alonso (2010)
The northeast area of São Paulo state was originally covered by cerrado and semideciduous forest, but for the last two centuries, it has experienced distinct cycles of human exploitation of its fertile soils. Despite of intensive human activities, large habitat loss and fragmentation of the native vegetation cover, pumas (Puma concolor) still inhabit remnant habitat fragments in the northeastern area of the state. In this study, by using fecal DNA and molecular markers, we investigated demographic and genetic issues on pumas to aggregate basic information for conservation efforts to maintain long term viable subpopulations of this toppredator in the region. Between 2004-2008, we identified 17 animals (13 females and four males) inhabiting two of the last natural refuges in the area; five females represented resident adults indicating that both refuge areas may act as a source of individuals in the landscape. Only three animals did not exhibit any degree of relatedness, and we found evidence of philopatry, behaviour already described in North American populations. By using mark-recapture-DNA-based methods, we estimated a density of 9.36 ± 2.54 animals/100 km2 inside and surrounding these areas (~260 km2), the largest density estimate for this species reported in the literature. The high abundance may reflect an absence of direct competitors, as well as large prey availability and absence of similar high quality patches in the matrix; mainly females tend to tolerate higher home-range overlap when many resources are available. Considering that pumas may disperse throughout the matrix, we quantified aspects that will probably have influence on the species viability in the area, such as roadkills (11; 10 males and one female) and puma-human conflicts (six events). Especially male pumas tend to disperse long distances from their natal area to occupy new home-ranges, avoiding inbreeding and maintaining high levels of gene flow. Thus, to qualify the dispersers movement success, in a higher geographic scale, we sampled 37 pumas and tested the hypothesis of lack of genetic structure among the natural areas in the region. We observed that pumas in the northeast area of São Paulo state constitute a single population, have high levels of genetic diversity (HE=0.79; mean of 10 alleles per locus) and are related to each other. We also found evidence of a recent bottleneck event in this 10 population. In spite of the huge landscape transformation in consequence of human activities, we concluded that pumas still maintain some levels of gene flow among the protected areas of the study area larger than 2,000 ha and more than 70 km distant one from another, so conservation efforts should be concentrated on the maintenance of this flow. We recommend that puma management should be conducted at the landscape level by increasing habitat connectivity, such as, (1) creating new protected areas; (2) applying an alternate cutting approach in eucalyptus plantations; (3) maintaining habitat patches in private properties; (4) creating structures to allow highway crossing of pumas; (5) designing educational actions to change community perception of large carnivores.